1975
DOI: 10.1128/jb.124.1.201-211.1975
|View full text |Cite
|
Sign up to set email alerts
|

Transformation analysis of three linkage groups in Staphylococcus aureus

Abstract: While studying a set of multiply marked mutants of Staphylococcus aureus strain 8325 by transformation, several instances of apparent genetic linkage were encountered. After showing that these linked transformations were readily inactivated by shearing of the deoxyribonucleic acid (DNA) but were resistant to dilution of the DNA, and showing that mixtures of DNA failed to form double transformants, it was concluded that the linkages were legitimate rather than the result of congression. Three linkage groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 26 publications
1
95
0
Order By: Relevance
“…For planktonic growth, S. aureus SH1000 (Horsburgh et al, 2002;O'Neill, 2010), a methicillin sensitive S. aureus was grown in Tryptic Soy Broth (TSB) or polyamine-free chemically defined medium (PN medium) (Pattee and Neveln, 1975) at 37°C, buffered to pH 7.0 from single colonies. The S. aureus SH1000 strain is derived from NCTC 8325 that had been cured of its three prophages to yield strain 8325-4, and thereafter the 8325-4 strain rsbU gene was repaired to yield strain SH1000 (Horsburgh et al, 2002).…”
Section: Bacterial Strains Media and Growth Conditionsmentioning
confidence: 99%
“…For planktonic growth, S. aureus SH1000 (Horsburgh et al, 2002;O'Neill, 2010), a methicillin sensitive S. aureus was grown in Tryptic Soy Broth (TSB) or polyamine-free chemically defined medium (PN medium) (Pattee and Neveln, 1975) at 37°C, buffered to pH 7.0 from single colonies. The S. aureus SH1000 strain is derived from NCTC 8325 that had been cured of its three prophages to yield strain 8325-4, and thereafter the 8325-4 strain rsbU gene was repaired to yield strain SH1000 (Horsburgh et al, 2002).…”
Section: Bacterial Strains Media and Growth Conditionsmentioning
confidence: 99%
“…Strains used in this work are listed in Table S1. Bacteria were generally cultivated in BHI Broth/Agar (Difco, Detroit, MI) or chemically defined PN media (Pattee and Neveln, 1975) in shaking cultures (250 r.p.m.) at 37°C.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Recently, Pattee and Glatz (1980) attempted to transform the e n t E phenotype in strain S6 and S. aureus C234. However since these determinants were apparently located outside the three linkage groups of known staphylococcal genes (see Pattee and Neveln 1975 for details of these mapping procedures), they were unable to convert a set of multiply-marked auxotrophic derivatives of NCTC 8325 to SEB' and the location of the genes governing SEB could not be determined. Even if they were successful, these experiments would be difficult to evaluate since our laboratory has shown that two determinants (pSN2 and the presumed SEB structural gene) are required for enterotoxigenesis.…”
Section: A Second Important Observation Was Made In the Experimentsmentioning
confidence: 99%